(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
What worries me is not that actors, playwrights, and critics are starting to put on performances, but that many of them are doing it better than some directors. It’s unfortunate that there are more and more amateur amateurs among the current directors.